The development of a harmony multisensory space based on reminiscence therapy to improve quality of life for older adults with dementia: A qualitative study - Fery Agusman Motuho Mendrofa; Dwi Indah Iswanti; Indah Wulaningsih; Hery Ernawati; Kristiana Susilowati (Physical Therapy Journal of Indonesia, 2025)
Introduction: Dementia significantly impacts elderly quality of life, necessitating innovative non-pharmacological approaches. This study aimed to identify key design elements for multisensory environments integrated with reminiscence therapy in Indonesian contexts. Methods: This qualitative study used an exploratory descriptive design through focus group discussions with 10 elderly participants, 2 family caregivers, and 5 healthcare professionals. Participants were selected through purposive sampling based on inclusion criteria established for this research protocol. Data were analyzed using Braun and Clarke's six-phase thematic analysis framework to identify key patterns related to the development of multisensory environments. Results: This study revealed five main themes from a comprehensive data analysis of therapeutic environments for the Indonesian population. These themes are: 1) the importance of positive reminiscence triggers to effectively stimulate memory, 2) the personal space requirements for comfort and safety as essential environmental design considerations, 3) the need for multisensory integration as a critical component of therapeutic environmental interventions, 4) the vital role of family support and communication strategies in a comprehensive care approach, and 5) the relevance of cultural and spiritual considerations in design to provide contextual meaning. Conclusion: The development of Harmony multisensory spaces should integrate reminiscence therapy principles with personalized design elements, emphasizing safety parameters, comfort metrics, and cultural sensitivity to effectively improve the quality of life for elderly individuals with dementia. Implementation requires multidisciplinary collaboration between healthcare professionals, designers, and family caregivers to ensure optimal therapeutic outcomes.